Measures to mitigate the main causes of social housing delays in Algeria - Zemra, Rachid; Saighi, Ouafa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Social housing in Algeria is carried out with state budget funds in order to eliminate social inequalities and guarantee a decent life to the citizen. However, delays have been observed in the realization. This study aims to examine the main causes and develop guidelines to effectively mitigate delays.
Keywords: Algeria; Social housing; Construction Projects; Delay causes; Mitigation measures